Value Relevance of Accounting Information and Stock Price Reaction: Empirical Evidence from China - Md. Jahidur Rahman; Ruoling Liu (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research question - This study investigates whether the release of financial accounting information is related to the change in stock prices. Motivation - The relationship between accounting information and stock price reaction is well documented in the United States and other major developed economies. However, what is the relationship between share prices and accounting information in emerging economies? According to the standards of Wall Street, London, and Tokyo, the emerging capital markets in the post-communist countries are very small, but they can be a major source of capital for economic growth and development. Idea - For investors, investment decisions about stock should be made by analyzing factors that can influence the stock price. Investors need to have information to determine whether they can benefit from the shares they bought. The financial condition of companies is one of the major information that investors should know. Data - We obtained data from the A-share market in Shanghai and Shenzhen Stock Exchange of 1,272 listed companies. Data from selected companies' annual report in 2008-2018 and closing share prices in 2009-2019 were collected. The sample data were from the China Stock Market and Accounting Research database. Tools - This study used a stepwise regression model to select variables that can provide significant effects and analyzed the regression of added variables and stock price. Findings - We find that value relevance of accounting number, profitability, liquidity, and operational efficiency are positively related to stock price reaction. Other accounting variables, such as earnings per share, current ratio, quick ratio, and debt to equity ratio, have a more significant influence on the market share price. A linear relationship is observed between stock prices and earning per share, current ratio, and quick ratio according to the stepwise regression method. Contribution - This study provides new insights for academic research and provides additional meaningful and useful information regarding the relevance of companies' accounting information for foreign and domestic investors, specifically domestic investors. This research has scientific and practical usefulness for investors who care about their returns on investments.
Keywords: M41; G14; 650; accounting information; profitability; liquidity; operational efficiency; leverage ability; the stock price